PENINGKATAN KETERAMPILAN MOTORIK HALUS MELALUI KEGIATAN MEMBATIK SEDERHANA MENGGUNAKAN PEWARNA ALAMI (PADA ANAK USIA 4-5 TAHUN DI TK ABABIL TANJUNG BATU) (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the suboptimal fine motor skills of children aged 4-5 years at Ababil Kindergarten Tanjung Batu, which is indicated by difficulties in using writing tools. This study aims to improve children's fine motor skills through simple batik activities using natural dyes. This study uses the Classroom Action Research model of Kemmis and McTaggart which is carried out in two cycles consisting of planning, action, observation, and reflection. The subjects of the study were 16 children (10 boys and 6 girls) in group A. Data were collected through observation and documentation and analyzed quantitatively and qualitatively. The results showed that simple batik activities using natural dyes improved children's fine motor skills, with classical improvements increasing from 33.20% in the pre-cycle to 54.37% in cycle I and 79.60% in cycle II.